Sago SENTRA PENGOLAHAN PATI SAGU DI KAMPUNG TAMBAT KABUPATEN MERAUKE - Puji Susanti PUJISUSANTI (AGRICOLA, 2020)
Abstract The potential of sago in Merauke Regency is very large when compared to other regions in Papua. Sago is a plant with high socio-cultural and economic values ​​in the Papuan community in general and for the Marind ethnic group in particular. Tambat processing centers in Merauke Regency only exist in Kampung Tambat, where almost all of these sago starch products are sold to meet market needs. However, due to limited production, it has not fulfilled market needs, this can be seen from the sago starch produced is always sold out. The purpose of this study was to obtain a picture of the sago processing business. Data collection techniques were carried out by field observations and interviews. The results of the study showed that there were two farmer groups namely the Marind and Mandobo groups who carried out sago plant development and sago starch processing activities. Sago processing technology is still traditionally carried out in stages: felling, stripping the skin, grating and extraction processes. The average income of a sago processor in a one-time processing that takes 3-4 days for the Marind group is Rp. 730,000 and the Mandobo group Rp. 680,000. Sago starch marketing is still limited to meet the needs of the local market. Keywords : processing sago starch; Tambat village